Bioinformatics protocol for teaching protein structure and function - Roggero, Airam [UNESP] (2024)
This study presents an alternative method for teaching protein function and structure in the classroom that exploits new technologies and facilities to provide active learning for students from Generation Z. This pedagogical approach is grounded in problem-based learning (PBL) as a self-directed study activity, proposed to be articulated in groups with the escort of well-oriented tutors. In this direction, the protocol was made for improving professors' capabilities that may be crucial for reducing communicative disparities between the interlocutors in Biochemistry classes and aims for developing early on, amongst the youth, autonomous critical thinking that consists of the basis for scientific knowledge construction. In accordance, the pilot lesson reported here considers the emergence of challenges from the information era as favorable scenery for advancement in teaching traditionally complex Chemistry concepts. With secretory phospholipase A2 as a simple 3D computational model for guidance, educators and students coordinate teamwork, unifying theory and practice via Bioinformatic tools, benefiting from new trends in modern science.